Argumentasi Pemikiran tentang Roh Perspektif Ibnul Qayyim Al-Jauziyah - Saifullah Saifullah; Ilham Yalin; Iskandar Arnel; Siti Soleha (AL-FIKRA, 2022)
Ibn al-Qayyim said that the spirit stands by itself. It can go up, down, relate, separate, leave, go, come, move, and be still. This study aims to discuss the spirit in Ibnul Qayyim Al-Jauziyah's view, starting from the perspective of the argument, rationale, advantages and disadvantages as well as criticism of his thoughts. This research is a library research and the approach method used in this research is a qualitative research approach. The data related to this study were collected through literature studies using qualitative data analysis methods. This research is presented with a technical descriptive analysis, namely by explaining related problems, by referring to the Koran as primary data and related literature books as secondary data. The results of this study indicate that Ibnul Qoyyim's thinking about spirit is a matter of absolute right from Allah alone. As long as this limb can still receive the influence arising from that gentle physicality, it remains with the members of the body, so that one feels the effects of feeling, movement and volition. If these members are corrupted by the oppressive component and cannot receive the influence then the soul separates from the body and passes to the spiritual realm. The spirit stood by itself. It can go up, down, relate, separate, leave, go, come, move, and be still. The body is a frame or a house for the spirit. So that the perfection of the body follows the perfection of the spirit.